1963
DOI: 10.1017/s0022143000028239
|View full text |Cite
|
Sign up to set email alerts
|

Observations of rapid water-level fluctuations in ice sink-hale lakes, Martin River Glacier, Alaska

Abstract: My article on mass budget terms was written to stimulate discussion so that a proper conceptual fram ework can be evolved. I believe that Dr. Glen has d efinitely contributed to this aim, and I would welcome further discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1965
1965
2005
2005

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Supraglacial outpourings of subglacially derived floodwater are a corollary of subglacial hydraulic transience [ Mathews , 1973; Roberts et al , 2000; Clarke , 2003], generated either by a temporary mechanical constriction [e.g., Reid and Clayton , 1963], a thermal boundary [ Skidmore and Sharp , 1999], or by a propagating wave of floodwater (section 3.3 and references therein). Supraglacial outbursts created during jökulhlaups emanate from a variety of outlet morphologies.…”
Section: Glacier Responses To Linearly Rising Jökulhlaupsmentioning
confidence: 99%
“…Supraglacial outpourings of subglacially derived floodwater are a corollary of subglacial hydraulic transience [ Mathews , 1973; Roberts et al , 2000; Clarke , 2003], generated either by a temporary mechanical constriction [e.g., Reid and Clayton , 1963], a thermal boundary [ Skidmore and Sharp , 1999], or by a propagating wave of floodwater (section 3.3 and references therein). Supraglacial outbursts created during jökulhlaups emanate from a variety of outlet morphologies.…”
Section: Glacier Responses To Linearly Rising Jökulhlaupsmentioning
confidence: 99%
“…Teller and Kehew (1995) concluded there was the potential for numerous subglacial outbursts of meltwater along the retreating Laurentide Ice Sheet. This may have occurred through sudden drainage of ice sinkhole lakes via subglacial channels, as observed by Reid and Clayton (1963). Coussot and Meunier (1996) concluded that such a sudden release of large volumes of water accompanying the drainage of an ice‐dammed lake could initiate a debris flow.…”
Section: Interpretations and Discussionmentioning
confidence: 82%
“…Publications by the University of North Dakota parties include reports by Reid and Clayton (1963), Clayton (1964), Tuthill ( 1963), Tuthill and Laird (1964), and Reid and Callender ( 1965) . Grantz, Plafker, and Kachadoorian (1964) and Post (1965) have discussed earthquake effects in the Martin-Bering Rivers area and Remnitz and Marshall (1966) have discussed the effects of the Alaskan earthquake on the unlithified sediments of the Copper River delta to the west of the area of this report.…”
Section: B2mentioning
confidence: 99%
“…In 1962 several ice-walled sinkhole lakes on the Lake Charlotte lobe of the Martin River glacier were drained of water (Reid and Clayton, 1963). Four of these lake basins were empty in July of 1963, but in June 1964 two were partially filled with water.…”
Section: Filling Of Ice-walled Sinkholesmentioning
confidence: 99%